A high-toughness composite TPU material and preparation method thereof
By organicizing the silicon dioxide and carbon nanopo pipes, it improves its decentralized and interface binding force in TPU materials, solving the problem of poor decentralization of silicon dioxide in TPU materials, significantly improved the stretching of TPU materials Power and breakdown rate.
Patent Information
- Application Number
- CN202410788775.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-18
AI Technical Summary
Silica as an inorganic filler has poor dispersion and limited interfacial binding force in organic polymers, which limits its application in TPU materials.
Through organic modification of silicon dioxide and carbon nanotubes, it improves its decentralization, compatibility, and interface binding force in the TPU material system, combined with the addition of modified silicon dioxide and modified carbon nanotubes to build three -dimensional Network structure.
It significantly improves the tensile strength and fracture and elongation of the TPU material, so that it has excellent strength and toughness.
Smart Images

Figure BDA0004899368620000101 
Figure BDA0004899368620000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of TPU materials and relates to a high-toughness composite TPU material and a preparation method thereof. Background Art
[0002] TPU is a thermoplastic polyurethane elastomer, a type of elastic polymer material containing multiple carbamates in the molecular chain. It is generally made from oligomer polyols, polyisocyanates, chain extenders / crosslinkers and some additives. The film made of TPU has excellent flexibility and can remain intact under large deformation; it has strong plasticity and can be processed and formed by heating, pressure and other methods, and has wide applicability; it has excellent wear resistance, etc. The many advantages of TPU film have made it widely used in fabrics, footwear, medical surgical gowns, protective clothing and other fields.
[0003] Silica (SiO2) is a commonly used nanofiller that can significantly improve the mechanical properties and thermal stability of polyurethane. However, as an inorganic filler, silica has poor dispersibility in organic polymers and limited interfacial bonding with polymers, which further limits its application in organic polymers. Summary of the invention
[0004] The object of the present invention is to provide a high-toughness composite TPU material and a preparation method thereof. The present invention organically modifies silicon dioxide and carbon nanotubes to increase the interaction between the two, while improving the dispersibility, compatibility and interface bonding strength of the two in the TPU material system, thereby significantly improving the tensile strength and elongation at break of the TPU material, so that the TPU material has excellent strength and toughness.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-toughness composite TPU material comprises the following components by weight: 90-110 parts of polyol, 58-64 parts of isocyanate, 12-15 parts of modified silicon dioxide, 8-11 parts of modified carbon nanotubes, 10-13 parts of chain extender, 3.3-4.5 parts of nano calcium carbonate, 1.2-1.5 parts of coupling agent and 4.0-5.6 parts of catalyst; wherein the coupling agent is coupling agent KH-550.
[0007] As a preferred technical solution of the present invention, the polyol is polytetramethylene glycol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is one or more of 1,4-butanediol, 1,3-propylene glycol and ethylenediamine; and the catalyst is dibutyltin dilaurate, stannous octanoate and stannous isooctanoate.
[0008] The present invention discloses a method for preparing the modified silicon dioxide, comprising the following steps:
[0009] Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then removing the solvent by rotary evaporation to obtain an aldehyde-modified coupling agent;
[0010] Step S2: After the nano-silica and anhydrous ethanol are stirred and mixed, an aldehyde-modified coupling agent is added and ultrasonically treated, and after heating and stirring, the mixture is placed in an oven for drying to obtain modified silica.
[0011] As a preferred technical solution of the present invention, in step S1, the stirring and mixing is stirring at a speed of 300-400 r / min for 15-20 min; the heating and irradiation is heating to 30-35°C and heating under 360-370nm ultraviolet lamp wavelength for 5-6h.
[0012] As a preferred technical solution of the present invention, in step S1, the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 27-30:10-13:20.0-22.4:1.0-1.6; the coupling agent is one or more of coupling agent KH-580, coupling agent KH-590, coupling agent Si-69 and coupling agent HD-112; and the initiator is photoinitiator 651.
[0013] As a preferred technical solution of the present invention, in step S2, the stirring and mixing is stirring at a speed of 600-800 r / min for 15-20 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 120-130 W for 5-8 min; the heating and stirring is stirring at a temperature of 60-70°C and a speed of 800-1000 r / min for 6-8 h; and the drying is drying at a temperature of 80°C to constant weight.
[0014] As a preferred technical solution of the present invention, in step S2, the mass ratio of the nano-silicon dioxide, anhydrous ethanol and aldehyde-modified coupling agent is 15-18:44-50:5-6.
[0015] The invention discloses a preparation method of the modified carbon nanotubes, comprising the following steps: in an inert atmosphere, carboxylating carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, centrifuged, washed, and placed in an oven for drying to obtain the modified carbon nanotubes.
[0016] As a preferred technical solution of the present invention, in the preparation of modified carbon nanotubes, the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1200-1400 r / min for 30-45 min; the heated stirring is stirring at a temperature of 70-75°C and a speed of 400-500 r / min for 5-6 h; the washing is alcohol washing; and the drying is drying at a temperature of 80°C to constant weight.
[0017] As a preferred technical solution of the present invention, in the preparation of modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 15-18:1.2-1.5:30-35:2.4-3.0:2.0-2.3:0.11-0.14; the initiator is one or two of azobisisobutyronitrile and azobisisoheptanenitrile.
[0018] The invention discloses a preparation method of a high-toughness composite TPU material. The preparation method comprises the following steps: mixing nano calcium carbonate and a coupling agent in a reaction kettle, adding polyol and a chain extender, heating and stirring the mixture, adding isocyanate and a catalyst, heating the mixture, adding modified silicon dioxide and modified carbon nanotubes, heating the mixture, and obtaining the high-toughness composite TPU material.
[0019] As a preferred technical solution of the present invention, the heating temperature is 60-70°C; the stirring and mixing is stirring at a speed of 300-400r / min for 9-15min; the heating treatment is heating at a temperature of 70-80°C for 3-5min; the temperature rising treatment is heating at a heating rate of 5-10°C / min to a temperature of 95-100°C for 4-6h.
[0020] Beneficial effects of the present invention:
[0021] The present invention organically modifies silicon dioxide and carbon nanotubes to increase the interaction between the two, and at the same time, by improving the dispersibility, compatibility and interface bonding force of the two in the TPU material system, significantly improves the tensile strength and elongation at break of the TPU material, so that the TPU material has excellent strength and toughness. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] Example 1
[0024] A high-toughness composite TPU material comprises the following components by weight: 90 parts of polyol, 58 parts of isocyanate, 12 parts of modified silicon dioxide, 8 parts of modified carbon nanotubes, 10 parts of chain extender, 3.3 parts of nano calcium carbonate, 1.2 parts of coupling agent and 4.0 parts of catalyst; wherein the polyol is polytetramethylene glycol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is 1,4-butanediol; and the catalyst is dibutyltin dilaurate.
[0025] The preparation method of the modified silicon dioxide comprises the following steps:
[0026] Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then evaporating the solvent to obtain an aldehyde-modified coupling agent; wherein the stirring and mixing is stirring at a speed of 300 r / min for 15 minutes; the heating and irradiation is heating to 30° C. and heating under a wavelength of 360 nm ultraviolet lamp for 5 hours; the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 27:10:20.0:1.0; the coupling agent is coupling agent KH-580; and the initiator is photoinitiator 651.
[0027] Step S2: After stirring and mixing the nano-silica and anhydrous ethanol, an aldehyde-modified coupling agent is added for ultrasonic treatment, and the mixture is heated and stirred and then placed in an oven for drying to obtain modified silica; wherein the stirring and mixing is stirring at a speed of 600 r / min for 15 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 120 W for 5 min; the heating and stirring is stirring at a temperature of 60° C. and a speed of 800 r / min for 6 h; the drying is drying at a temperature of 80° C. to constant weight; and the mass ratio of the nano-silica, anhydrous ethanol and the aldehyde-modified coupling agent is 15:44:5.
[0028] The preparation method of the modified carbon nanotubes comprises the following steps:
[0029] In an inert atmosphere, carboxylated carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, the mixture is centrifuged, washed and dried in an oven to obtain modified carbon nanotubes; wherein the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1200 r / min for 30 min; the heating and stirring is stirring at a temperature of 70°C and a speed of 400 r / min for 5 h; the washing is alcohol washing; the drying is drying at a temperature of 80°C to constant weight, and the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 15:1.2:30:2.4:2.0:0.11; and the initiator is azobisisobutyronitrile.
[0030] A preparation method of a high-toughness composite TPU material comprises the following steps: mixing nano calcium carbonate and a coupling agent in a reaction kettle, adding a polyol and a chain extender, heating and stirring the mixture, adding an isocyanate and a catalyst for heating treatment, adding modified silicon dioxide and modified carbon nanotubes for heating treatment, and obtaining a high-toughness composite TPU material; wherein the heating temperature is 60°C; the stirring and mixing is stirring at a speed of 300 r / min for 9 minutes; the heating treatment is heating at a temperature of 70°C for 3 minutes; and the heating treatment is heating at a heating rate of 5°C / min to a temperature of 95°C for 4 hours.
[0031] Example 2
[0032] A high-toughness composite TPU material comprises the following components by weight: 97 parts of polyol, 60 parts of isocyanate, 13 parts of modified silicon dioxide, 9 parts of modified carbon nanotubes, 11 parts of chain extender, 3.7 parts of nano calcium carbonate, 1.3 parts of coupling agent and 4.5 parts of catalyst; wherein the polyol is polytetramethylene glycol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is 1,4-butanediol; and the catalyst is dibutyltin dilaurate.
[0033] The preparation method of the modified silicon dioxide comprises the following steps:
[0034] Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then evaporating the solvent to obtain an aldehyde-modified coupling agent; wherein the stirring and mixing is stirring at a speed of 330 r / min for 17 minutes; the heating and irradiation is heating to 32° C. and heating under a wavelength of 363 nm ultraviolet lamp for 5.5 hours; the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 28:11:20.8:1.2; the coupling agent is coupling agent KH-580; and the initiator is photoinitiator 651.
[0035] Step S2: After stirring and mixing the nano-silica and anhydrous ethanol, an aldehyde-modified coupling agent is added for ultrasonic treatment, and the mixture is heated and stirred and then placed in an oven for drying to obtain modified silica; wherein the stirring and mixing is stirring at a speed of 667 r / min for 17 minutes; the ultrasonic treatment is ultrasonic treatment at a frequency of 123 W for 6 minutes; the heating and stirring is stirring at a temperature of 63° C. and a speed of 867 r / min for 6.7 hours; the drying is drying at a temperature of 80° C. to constant weight; and the mass ratio of the nano-silica, anhydrous ethanol and aldehyde-modified coupling agent is 16:46:5.3.
[0036] The preparation method of the modified carbon nanotubes comprises the following steps:
[0037] In an inert atmosphere, carboxylated carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, the mixture is centrifuged, washed and dried in an oven to obtain modified carbon nanotubes; wherein the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1260 r / min for 35 min; the heating and stirring is stirring at a temperature of 72°C and a speed of 430 r / min for 5.5 h; the washing is alcohol washing; the drying is drying at a temperature of 80°C to constant weight, and the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 16:1.3:32:2.6:2.1:0.12; and the initiator is azobisisobutyronitrile.
[0038] A preparation method of a high-toughness composite TPU material comprises the following steps: mixing nano calcium carbonate and a coupling agent in a reaction kettle, adding a polyol and a chain extender, heating and stirring the mixture, adding an isocyanate and a catalyst for heating treatment, adding modified silicon dioxide and modified carbon nanotubes for heating treatment, and obtaining a high-toughness composite TPU material; wherein the heating temperature is 63°C; the stirring and mixing is stirring at a speed of 333 r / min for 11 minutes; the heating treatment is heating at a temperature of 73°C for 3 minutes; and the heating treatment is heating at a heating rate of 7°C / min to a temperature of 97°C for 4.5 hours.
[0039] Example 3
[0040] A high-toughness composite TPU material comprises the following components by weight: 103 parts of polyol, 62 parts of isocyanate, 14 parts of modified silicon dioxide, 10 parts of modified carbon nanotubes, 12 parts of chain extender, 4.1 parts of nano calcium carbonate, 1.4 parts of coupling agent and 5.1 parts of catalyst; wherein the polyol is polytetramethylene ether diol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is 1,4-butanediol; and the catalyst is dibutyltin dilaurate.
[0041] The preparation method of the modified silicon dioxide comprises the following steps:
[0042] Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then evaporating the solvent to obtain an aldehyde-modified coupling agent; wherein the stirring and mixing is stirring at a speed of 360 r / min for 18 minutes; the heating and irradiation is heating to 33° C. and heating under a wavelength of 367 nm ultraviolet lamp for 5.5 hours; the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 29:12:21.6:1.4; the coupling agent is coupling agent KH-580; and the initiator is photoinitiator 651.
[0043] Step S2: After stirring and mixing the nano-silica and anhydrous ethanol, add an aldehyde-modified coupling agent for ultrasonic treatment, heat and stir, and then place in an oven for drying to obtain modified silica; wherein the stirring and mixing is stirring at a speed of 730 r / min for 18 minutes; the ultrasonic treatment is ultrasonic treatment at a frequency of 125 W for 7 minutes; the heating and stirring is stirring at a temperature of 67°C and a speed of 930 r / min for 7.5 hours; the drying is drying at a temperature of 80°C to constant weight; the mass ratio of the nano-silica, anhydrous ethanol and aldehyde-modified coupling agent is 17:48:5.7.
[0044] The preparation method of the modified carbon nanotubes comprises the following steps:
[0045] In an inert atmosphere, carboxylated carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, the mixture is centrifuged, washed and dried in an oven to obtain modified carbon nanotubes; wherein the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1300r / min for 40min; the heating and stirring is stirring at a temperature of 73°C and a speed of 465r / min for 5.5h; the washing is alcohol washing; the drying is drying at a temperature of 80°C to constant weight, and the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 17:1.4:33:2.8:2.2:0.13; and the initiator is azobisisobutyronitrile.
[0046] A preparation method of a high-toughness composite TPU material comprises the following steps: mixing nano calcium carbonate and a coupling agent in a reaction kettle, adding a polyol and a chain extender, heating and stirring the mixture, adding an isocyanate and a catalyst for heating treatment, adding modified silicon dioxide and modified carbon nanotubes for heating treatment, and obtaining a high-toughness composite TPU material; wherein the heating temperature is 67°C; the stirring and mixing is stirring at a speed of 365 r / min for 13 min; the heating treatment is heating at a temperature of 77°C for 4 min; and the heating treatment is heating at a heating rate of 8°C / min to a temperature of 98°C for 5.5 h.
[0047] Example 4
[0048] A high-toughness composite TPU material comprises the following components by weight: 110 parts of polyol, 64 parts of isocyanate, 15 parts of modified silicon dioxide, 11 parts of modified carbon nanotubes, 13 parts of chain extender, 4.5 parts of nano calcium carbonate, 1.5 parts of coupling agent and 5.6 parts of catalyst; wherein the polyol is polytetramethylene ether diol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is 1,4-butanediol; and the catalyst is dibutyltin dilaurate.
[0049] The preparation method of the modified silicon dioxide comprises the following steps:
[0050] Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then evaporating the solvent to obtain an aldehyde-modified coupling agent; wherein the stirring and mixing is stirring at a speed of 400 r / min for 20 minutes; the heating and irradiation is heating to 35° C. and heating under a wavelength of 370 nm ultraviolet lamp for 6 hours; the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 30:13:22.4:1.6; the coupling agent is coupling agent KH-580; and the initiator is photoinitiator 651.
[0051] Step S2: After stirring and mixing the nano-silica and anhydrous ethanol, add an aldehyde-modified coupling agent for ultrasonic treatment, heat and stir, and then place in an oven for drying to obtain modified silica; wherein the stirring and mixing is stirring at a speed of 800 r / min for 20 minutes; the ultrasonic treatment is ultrasonic treatment at a frequency of 130 W for 8 minutes; the heating and stirring is stirring at a temperature of 70°C and a speed of 1000 r / min for 8 hours; the drying is drying at a temperature of 80°C to constant weight; the mass ratio of the nano-silica, anhydrous ethanol and the aldehyde-modified coupling agent is 18:50:6.
[0052] The preparation method of the modified carbon nanotubes comprises the following steps:
[0053] In an inert atmosphere, carboxylated carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, the mixture is centrifuged, washed and dried in an oven to obtain modified carbon nanotubes; wherein the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1400 r / min for 45 min; the heating and stirring is stirring at a temperature of 75°C and a speed of 500 r / min for 6 h; the washing is alcohol washing; the drying is drying at a temperature of 80°C to constant weight, and the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 18:1.5:35:3.0:2.3:0.14; and the initiator is azobisisobutyronitrile.
[0054] A preparation method of a high-toughness composite TPU material comprises the following steps: mixing nano calcium carbonate and a coupling agent in a reaction kettle, adding a polyol and a chain extender, heating and stirring the mixture, adding an isocyanate and a catalyst, heating the mixture, adding modified silicon dioxide and modified carbon nanotubes, heating the mixture, and obtaining a high-toughness composite TPU material; wherein the heating temperature is 70°C; the stirring and mixing is performed at a speed of 400 r / min for 15 minutes; the heating treatment is performed at a temperature of 80°C for 5 minutes; and the heating treatment is performed at a heating rate of 10°C / min to a temperature of 100°C for 6 hours.
[0055] Comparative Example 1
[0056] Compared with Example 3, the difference in Comparative Example 1 is that step S1 of Comparative Example 1 does not use cinnamaldehyde, and the other components, preparation steps and parameters are the same.
[0057] Comparative Example 2
[0058] Compared with Example 3, the difference of Comparative Example 2 is that no coupling agent is used in step S1 of Comparative Example 2, and the other components, preparation steps and parameters are the same.
[0059] Comparative Example 3
[0060] Compared with Example 3, the difference of Comparative Example 3 is that Comparative Example 3 uses nano-silica instead of modified silica, and the other components, preparation steps and parameters are the same.
[0061] Comparative Example 4
[0062] Compared with Example 3, Comparative Example 4 is different in that no acrylamide is used in Comparative Example 4, and the other components, preparation steps and parameters are the same.
[0063] Comparative Example 5
[0064] Compared with Example 3, the difference in Comparative Example 5 is that cardanol is not used in Comparative Example 5, and the other components, preparation steps and parameters are the same.
[0065] Comparative Example 6
[0066] Compared with Example 3, the difference in Comparative Example 6 is that Comparative Example 6 does not use styrene, and the other components, preparation steps and parameters are the same.
[0067] Comparative Example 7
[0068] Compared with Example 3, the difference of Comparative Example 7 is that Comparative Example 7 uses carboxylated carbon nanotubes instead of modified carboxylated carbon nanotubes, and the other components, preparation steps and parameters are the same.
[0069] Mechanical properties test:
[0070] According to GB / T13022-1991, the composite TPU materials obtained in Examples 1-4 and Comparative Examples 1-7 were cut into dumbbell-shaped strips with a cutter, and the width and thickness of the film were measured with a vernier caliper. The film was stretched at a speed of 300 mm / min using a tensile testing machine, and the tensile strength and elongation at break of the film were recorded. The test results are shown in Table 1.
[0071] Table 1 Mechanical properties test results
[0072]
[0073]
[0074] As can be seen from the test results in Table 1, compared with Comparative Examples 1-7, the tensile strength and elongation at break of the high-toughness composite TPU materials obtained in Examples 1-4 of the present invention are better than those in Comparative Examples 1-6. This is because, in the present invention, cardanol acts as a chain extender in the preparation of TPU materials, which can form longer polymer carbon chains, increase the molecular weight of the TPU material, and make it have better mechanical properties. It has a higher grafting rate in combination with styrene, increases the dispersibility and compatibility of carbon nanotubes in the TPU material system, and introduces amino groups in acrylamide, which can not only react with isocyanate, but also interact with imine bonds, so that silicon dioxide can be evenly dispersed in the TPU material, thereby significantly improving the tensile strength and elongation at break. The addition of modified silicon dioxide and modified carbon nanotubes can effectively crosslink with the polyurethane chains in the TPU material, thereby building a three-dimensional network structure. This innovative measure significantly enhances the strength and hardness of the material, greatly improves its ability to resist tensile fracture, and thus effectively strengthens the tensile strength and elongation at break of the TPU material. At the same time, modified silica and modified carbon nanotubes can also increase the viscosity and viscosity of the system through filling, further ensuring the stability of the TPU material.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-toughness composite TPU material, characterized in that: The following components are included by weight: 90-110 parts of polyol, 58-64 parts of isocyanate, 12-15 parts of modified silicon dioxide, 8-11 parts of modified carbon nanotubes, 10-13 parts of chain extender, 3.3-4.5 parts of nano calcium carbonate, 1.2-1.5 parts of coupling agent and 4.0-5.6 parts of catalyst; The preparation method of the modified silicon dioxide comprises the following steps: Step S1: placing cinnamaldehyde, anhydrous ethanol and a coupling agent in a reaction kettle, stirring and mixing, adding an initiator, heating and irradiating, and then removing the solvent by rotary evaporation to obtain an aldehyde-modified coupling agent; the coupling agent is one or more of coupling agent KH-580, coupling agent KH-590 and coupling agent HD-112; Step S2: After the nano-silicon dioxide and anhydrous ethanol are stirred and mixed, an aldehyde-modified coupling agent is added and ultrasonically treated, and after heating and stirring, the mixture is placed in an oven for drying to obtain modified silicon dioxide; The preparation method of the modified carbon nanotubes comprises the following steps: in an inert atmosphere, carboxylating carbon nanotubes, acrylamide and anhydrous ethanol are stirred at high speed, styrene and cardanol are added and stirred and mixed, an initiator is added and heated and stirred, centrifuged, washed, and placed in an oven for drying to obtain the modified carbon nanotubes.
2. A high-toughness composite TPU material according to claim 1, characterized in that: The polyol is polytetramethylene ether diol with a molecular weight of 1000; the isocyanate is toluene diisocyanate; the chain extender is one or more of 1,4-butanediol, 1,3-propylene glycol and ethylenediamine; and the catalyst is dibutyltin dilaurate, stannous octanoate and stannous isooctanoate.
3. A high-toughness composite TPU material according to claim 1, characterized in that: In step S1, the stirring and mixing is stirring at a speed of 300-400 r / min for 15-20 min; the heating and irradiation is heating to 30-35° C. and heating for 5-6 h under irradiation of a 360-370 nm ultraviolet lamp.
4. The high-toughness composite TPU material according to claim 1, characterized in that: In step S1, the mass ratio of cinnamaldehyde, anhydrous ethanol, coupling agent and initiator is 27-30:10-13:20.0-22.4:1.0-1.6; the initiator is photoinitiator 651.
5. The high-toughness composite TPU material according to claim 1, characterized in that: In step S2, the stirring and mixing is stirring at a speed of 600-800 r / min for 15-20 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 120-130 W for 5-8 min; the heating and stirring is stirring at a temperature of 60-70° C. and a speed of 800-1000 r / min for 6-8 h; and the drying is drying at a temperature of 80° C. to constant weight.
6. The high-toughness composite TPU material according to claim 1, characterized in that: In step S2, the mass ratio of the nano-silica, anhydrous ethanol and aldehyde-modified coupling agent is 15-18:44-50:5-6.
7. The high-toughness composite TPU material according to claim 1, characterized in that: In the preparation of modified carbon nanotubes, the inert atmosphere is a nitrogen atmosphere; the high-speed stirring is stirring at a speed of 1200-1400 r / min for 30-45 min; the heated stirring is stirring at a temperature of 70-75°C and a speed of 400-500 r / min for 5-6 h; the washing is alcohol washing; and the drying is drying at a temperature of 80°C to constant weight.
8. The high-toughness composite TPU material according to claim 1, characterized in that: In the preparation of modified carbon nanotubes, the mass ratio of the carboxylated carbon nanotubes, acrylamide, anhydrous ethanol, styrene, cardanol and initiator is 15-18:1.2-1.5:30-35:2.4-3.0:2.0-2.3:0.11-0.14; the initiator is one or two of azobisisobutyronitrile and azobisisoheptanenitrile.
9. A method for preparing a high-toughness composite TPU material as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: placing nano calcium carbonate and a coupling agent in a reaction kettle and mixing them, adding polyol and a chain extender, heating and stirring to mix, adding isocyanate and a catalyst to perform a heating treatment, adding modified silicon dioxide and modified carbon nanotubes and performing a heating treatment to obtain a high-toughness composite TPU material.
10. The method for preparing a high-toughness composite TPU material according to claim 9, characterized in that: The heating temperature is 60-70°C; the stirring and mixing is stirring at a speed of 300-400r / min for 9-15min; the heating treatment is heating at a temperature of 70-80°C for 3-5min; the temperature rising treatment is heating at a heating rate of 5-10°C / min to a temperature of 95-100°C for 4-6h.
Citation Information
Patent Citations
Curable Resin Composition and Cold Setting Adhesive
US20090264602A1
Silane / urea compound as a heat-activated curing agent for epoxide resin compositions
US20140216655A1